Optimization of the Effectiveness of Treatment of Allergic Rhinitis, Which is Complicated by Adenoiditis in Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Between 2020 and 2022, scientific research was carried out on 60 children who applied to the LOR-Department of the Bukhara region children's Multidisciplinary Medical Center. The first group included 30 patients: allergic rhinitis, persisting form. Adenoiditis. Hypertrophy of the pharyngeal tonsil has been the subject of a traditional conservative treatment with Grade II-III diagnosis. Patients of the second group: allergic rhinitis, persistivating form. Adenoiditis. Endonasal flutynex spray was adopted as the traditional treatment with hypertrophy of the pharyngeal tonsil Grade II - III diagnosis did not benefit.Complex stepwise conservative treatment of children with adenoiditis and allergic rhinitis, including the use of topical corticosteroids and cephalosporins of the second generation, demonstrated a high therapeutic effect in 55.9% of patients, which was confirmed by reliable improvements in the indicators of anterior active rhinomanometry and endoscopic picture and allowed to cancel the adenotomy.